Ist das Hautfarbe? Elementarpädagogische Präventionsmaßnahmen gegen Vorurteile und Diskriminierung bei Kindern - Stärck, Alexander (promotion, 2019)
"Is that skin color?" Even young children use differences as the basis for prejudiced thoughts, which are expressed in discriminatory actions. For the study, the author visited day care centers where educational measures against prejudice and discrimination are used. But how does prevention work? The study evaluates videographed everyday situations and group discussions in a documentary manner and thus provides specialist practice and science with a basis for further discussion of the socially relevant topic.